2018
DOI: 10.5204/ssj.v9i3.465
|View full text |Cite
|
Sign up to set email alerts
|

The long and winding road: Experiences of students entering university through transition programs

Abstract: This article presents outcomes of two studies which focus on the lived experience of transition by students entering higher education in NSW (New South Wales), Australia, from two divergent pathways: Technical and Further Education (TAFE) and a university based enabling program. The studies intersect in two fundamental ways. First, the theoretical foundations (Mezirow’s Transformational Learning Theory and Bourdieu’s Social Capital Theory) which emphasise the role of habits of mind and the habitus respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…An additional implication of undecidedness concerns the fact that it may block students' agency conceived as either life plans competence or self-efficacy. This is verified by Millman and McNamara (2018) whose research has shown that the determination to act in an agentic way in challenging situations (such as the decision about university studies) is put in jeopardy whenever one is uncertain about his goals. Besides the fact that undecidedness puts students' first-year adjustment to the university in jeopardy and blocks their agency, it differentiates them in relation to how they approach university studies.…”
Section: Discussionmentioning
confidence: 85%
“…An additional implication of undecidedness concerns the fact that it may block students' agency conceived as either life plans competence or self-efficacy. This is verified by Millman and McNamara (2018) whose research has shown that the determination to act in an agentic way in challenging situations (such as the decision about university studies) is put in jeopardy whenever one is uncertain about his goals. Besides the fact that undecidedness puts students' first-year adjustment to the university in jeopardy and blocks their agency, it differentiates them in relation to how they approach university studies.…”
Section: Discussionmentioning
confidence: 85%
“…To help students positively adapt to the new context, universities usually implement actions aimed at creating optimal conditions for student well-being. The first year at university involves several important changes in the educational environment, such as unknown academic tasks, new relationships and social expectations, more academic competition, and a novel identity [ 1 , 2 ]. Moving to a higher level of education may cause concern among college students because it involves a transition to adulthood and a new, complex context that can negatively influence their ability or willingness to stay on an academic course [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%